DIGESTIVE HEMORRHAGE IN PEDIATRICS - DIAGNOSTIC CHALLENGES IN A SMALL TODDLER WITH MECKEL'S DIVERTICULUM - Smaranda Diaconescu; Ana-Maria Scurtu; Lorenza Donea; Andreea Nechita; Oana-Maria Rosu; Gabriela Ghiga; Nicoleta Gimiga; Silvia Strat (Romanian Society of Oral Rehabilitation, 2020)
Digestive hemorrhage among the pediatric population is one of the most important causes of addressability to pediatric emergency medical services, being, due to its complexity, a real challenge for the clinician. Precise and early diagnosis and therapeutic conduct are life-saving. We present a case of Meckel's diverticulum in a 9-month-old male infant with a history of upper gastrointestinal bleeding exteriorized as hematemesis 2 month prior to current admission. The recurrence of melena with posthemorhagic severe anemia imposed an upper digestive endoscopy that did not identify active sources of bleeding or stigmas of recent bleeding. The suspicion of a Meckel's diverticulum was raised and scintigraphy was recommended but as the infant's general condition deteriorates, surgery was required. Intraoperatively, the presence of a Meckel diverticulum with umbilical adhesions is noticeable.